KREATIVITAS KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGAPLIKASIKAN KEMAMPUAN MEMBACA AL-QUR’AN ANAK USIA DINI PADA MASA NEWNORMAL - Mesran Mesran; Hotni Sari Harahap; Ade Tursina (UIR PRESS, 2022)
This research is a field research with a qualitative descriptive method, the subject and informants are the principal and teachers and children of group B at RA Hidayatus Shibyaan, which is located on Jln. Veterans Market 6 Manunggal Kab. Deli Serdang. Data collection methods used is observation, interviews and documentation. The results showed that the implementation of the creativity of the principal of RA Hidayatus Shibyaan in applying the ability to read the Al-Qur’an for children, namely through the guidance of RA teachers holding meetings, teacher professional training, direct monitoring of the learning process, and the implementation of al-Al-Qur’an learning with the Iqro method through daily routine. The inhibiting factors in the implementation of creativity are work, less enthusiastic responses from stakeholders, and internal and external motivation. While the supporting factors are good cooperation between stakeholders, positive emotion teachers, the completeness of the Koran learning media, a comfortable and harmonious work environment, and the implementation of an effective